Texts and technologies in Chinese silver metallurgy, twelfth to nineteenth centuries - Yang, Yuda; Kim, Nanny (East Asian science, technology, and medicine, 2019)
The silver metallurgy of late imperial China has rarely been the subject of specific studies because silver exploitation has long been considered of minor importance and traditional sources are scarce. This article is an attempt at filling the research gap of the period from the Song to the late Qing. With a focus on the silver mines of the Southwest and the adjoining borderlands and employing an approach that combines textual analysis with the study of remains and oral histories, it presents a systematic discussion of process steps and traces technological transformations.